Microstructure and Mechanical Property Correlation Between Rotary Friction Welded Nitinol–Nitinol Joints - Rehman, Ateekh Ur; Babu, Nagumothu Kishore; Talari, Mahesh Kumar; Usmani, Yusuf Siraj; Al-Khalefah, Hisham (Frontiers in Materials, 2021)
In the present study, a rotary friction process was used to join nitinol in a similar welding combination. Macro- and microstructure characteristics of the weld zone were compared with adjacent zones and the base metal. The hardness and tensile properties of the joints were evaluated, and the results were discussed in relation to the weld microstructure. The weld macrostructure revealed a uniform flash around the circumference of the weld. The optical microstructure of the welded sample revealed fine recrystallized grains at the weld interface due to heavy deformation followed by dynamic recrystallization. The phase transformation behavior of the base metal and welded samples was studied by using a differential scanning calorimeter (DSC). The drift in phase transformation temperatures after rotary friction welding may be attributed to fine grain formation at the weld interface. Friction welded samples exhibited improved yield strength and hardness values compared to the base metal due to grain refinement at the weld interface.